Radon exposure risks among residents proximal to gold mine tailings in Gauteng Province, South Africa: a cross-sectional preliminary study protocol - Mphaga, Khathutshelo Vincent; Utembe, Wells; Rathebe, Phoka Caiphus (Frontiers in Public Health, 2024)
Gold mine tailings, a legacy of the mining industry, harbours significant amount of radon gas, a classified human carcinogen. Radon exposure, especially near tailings, is a significant public health threat, potentially leading to increased risk of lung cancer, leukaemia, and chronic obstructive pulmonary disease (COPD). These health problems are often associated with lower survival rates and significant financial burdens. This ongoing research aim to evaluating the relationship between indoor radon exposure and lung cancer, leukaemia, and COPD risks amongst residents proximal to gold mine tailings in Gauteng Province, South Africa. This cross-sectional preliminary study focus on two distinct groups: Riverlea (exposed group, <2 kilometres (km) to Gold mine tailings) and Orlando East (unexposed group, >2 km to Gold mine tailings). Indoor radon levels is measured using AlphaE monitors, while health risks (lung cancer, leukaemia, COPD) linked to exposure are evaluated through interview-administered questionnaire and secondary data from Gauteng Health Department. Of the 476 residents randomly selected for this study, 300 have already participated, with balanced representation from both the exposed and unexposed groups. The study will compare indoor radon levels and health outcomes between the two groups. This study's results could aid in creating targeted interventions and policies to mitigate indoor radon exposure risks and safeguard vulnerable communities from this significant public health hazard.